Zapisz wyrażenia, nie używając nawiasów.Zredaguj wyrazy podobne.

a) x+(3x-y² +7)
b) -a+(2a-3b-1)
c) -x do 2 +(x² - x - 7)
d) -b³ - (b³ - b² - b)
e) (2a - 3b) + (4a-b)
f) -(x² - 3x)+(x²+3x)
g) (a+b - c)-(2a-b+2c)
h) -(x² -xy-z)-(-x² +2xy + 2z)
bardzo proszę o szybką pomoc

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-06T14:59:08+01:00
A) x+(3x-y² +7) = x +3x-y²+7 = 4x-y²+7
b) -a+(2a-3b-1) = -a+2a-3b-1 = a-3b-1
c) -x do 2 +(x² - x - 7) = -x do 2+x²-x-7 = 1 do 2+x²-7
d) -b³ - (b³ - b² - b) =-b³ -b³+b²+b = -2b³ +b²+b
e) (2a - 3b) + (4a-b) = 2a - 3b +4a-b = 6a-4b
f) -(x² - 3x)+(x²+3x) = -x² + 3x +x²+3x = 6x
g) (a+b - c)-(2a-b+2c) = a+b-c-2a+b-2c=2b - a - 3c
h) -(x² -xy-z)-(-x² +2xy + 2z) = -x² +xy+z +x² -2xy - 2z = -xy-2z
4 5 4
2010-01-06T14:59:31+01:00
A)4x-y to y do kwadratu+7
b)a-3b-1
c)-x-7
e)8a do 2+2ab-12ab+3b do 2
4 1 4